A robust numerical method for granular hydrodynamics in three dimensions - Shakeri, Ali; Schiochet Nasato, Daniel; Müller, Patric; Torres Menendez, Harol; Pöschel, Thorsten (Journal of Fluid Mechanics, 2021)
Granular systems are of a discrete nature. Nevertheless, it can be advantageous to describe their dynamics by means of continuum mechanical methods. The numerical solution of the corresponding hydrodynamic equations is, however, difficult. Therefore, previous numerical simulations are typically geared towards highly specific systems and frequently restricted to two dimensions or mild driving conditions. Here, we present the first robust general simulation scheme for granular hydrodynamics in three dimensions which is not bound to the above limitations. The performance of the simulation scheme is demonstrated by means of three applications which have been proven as notoriously difficult for numerical hydrodynamic description. Although, by construction, our numerical method covers grain-inertia flows, the presented examples demonstrate that it produces reliable results even in the jammed or high density limit.
CRIS-Team Scopus Importer:2021-05-14
Keywords: granular media

Limitation of stochastic rotation dynamics to represent hydrodynamic interaction between colloidal particles - Shakeri, Ali; Lee, Kuang-Wu; Pöschel, Thorsten (Physics of Fluids, 2018)
Stochastic Rotation Dynamics (SRD) is a valuable numerical tool extensively used in many domains of hydrodynamics simulations including colloidal suspensions. We investigate the dynamics of two colloidal particles in the regime of low Reynolds number by means of SRD in 3D. In contrast to well-known analytical and experimental results, no long-range interaction between the suspended particles could be found, independent of the size of the particles and the Mach and Péclet numbers. We attribute this behavior to the compressible nature and low sound velocity in the SRD solvent. The inability of representing long-range interactions poses an important limitation to the applicability of SRD to certain physical systems. We provide an estimation of typical length scales for which SRD can be applied.